QUESTIONING THE SOCIAL SERVICES IN TURKEY THROUGH RAPE SURVIVORS - Göçmener, Sinem; Akkuş, Pınar (PEOPLE: International Journal of Social Sciences, 2017)
In Turkey, policies are mainly based on strengthening family ties which actually weaken women’s positions in every aspect of life and there is still no gender equality in law especially in practice. Social policies and institutions in Turkey are not so much supportive of women or focusing on the needs of women. This stems from the social structure which mostly concerns men’s needs. Raping women is a part of systematic and political violence in Turkey. Our research aims to examine what conditions women are in and suffer through in Turkey when they have been raped or exposed to sexual violence.A woman has to deal with the patriarchal structure in every step of reporting procedure to the police and prosecution officer in the process of forensics to get a report when she has been raped. It means that she experiences the same trauma over and over again. Women are questioned as offenders rather than victims. Hence, women avoid reporting their cases in the first place, and of course this happens when the case did not end with death However, lack of emergency response plan for rape survivors in Turkey is the main issue of this work. We need rape crisis centres established under the Ministry of Family and Social Policies (ASPB) and Ministry of Health or a network of NGOs and research centres in universities. However, Turkish government does not set budget for such centres. This is another concern of our research. This study mainly aims to investigate the legislation of rape crime and to argue the issues on implementations of international conventions on preventing and combating violence against women. It also presents the results of the interviews carried out with NGOs working on sexual violence.